(untitled) (Eurasian Journal of Humanities and Social Sciences, 2022)
Today, a modern school should prepare such a person who not only has knowledge, but also knows how to use his/her acquired knowledge in life, knows how to communicate in social settings. The goal is not for the child to know how as much as possible, but that he was able to act and solve problems in any situation. Mastery of language and speech is a necessary condition for the formation of a socially active personality. To learn to speak clearly and grammatically correctly, to have a well-trained voice, to express one’s own thoughts in a free creative interpretation in oral and written form, to be able to express one’s emotions by various intonation means, to observe speech culture and develop the ability to communicate is necessary for everyone. Therefore, one of the most important tasks at the present stage of teaching children is the development of speech activity. This article provides an overview how to develop the speech of elementary school children, how to improve phonemic skills in Russian classes